A retrospective review of CTPA confirmed pulmonary emboli in COVID-19 patients admitted to Groote Schuur Hospital, Cape Town - Ahlers, Petri (Division of Radiology, 2025)
Background: A high incidence of thromboembolic phenomena has been widely reported in patients with COVID-19 pneumonia. There is, however, a paucity of data detailing the incidence and characteristics of pulmonary emboli (PE) in COVID-19 patients in the South African setting. An improved understanding of the presentation and course of these patients is warranted, considering the serious and potentially fatal outcomes. Objectives: To describe the incidence and characteristics of PE confirmed by Computer Tomography Pulmonary Angiogram (CTPA) in patients with COVID-19 pneumonia admitted to a tertiary hospital in the Western Cape, South Africa. Methods: We performed a retrospective-, descriptive study of all adult patients with COVID-19 pneumonia confirmed by Polymerase Chain Reaction (PCR) undergoing CTPA for suspected PE while admitted to Groote Schuur Hospital. The study period was from 1 April 2020 to 30 September 2020. Results: Our study cohort consisted of 116 patients, 59% being female, of whom, 29% were pregnant or in the postpartum period. The median age for both genders combined was 49.5 years. The overall incidence of PE was 19 %, with 20 % in our subset of pregnant and postpartum patients. The majority (64%) of PE's were reported as being segmental in anatomical location. Conclusion: Our study cohort was noteworthy in including pregnant and postpartum patients. The overall incidence of PE was 19 % with no significant differences in demographics, comorbidities or D-dimer levels between patients with or without PE. The importance of a high clinical index of suspicion together with the role of CTPA in diagnosing PE in hospitalised COVID-19 patients is emphasised.